2010
DOI: 10.1007/s00213-010-1857-0
|View full text |Cite
|
Sign up to set email alerts
|

MD-354 selectively antagonizes the antinociceptive effects of (−)nicotine in the mouse tail-flick assay

Abstract: MD-354 selectively antagonizes the antinociceptive actions of (-)nicotine in the tail-flick, but not in the hot-plate assay, or either the motor effects, or discriminative stimulus effects of (-)nicotine. The most parsimonious explanation is that MD-354 might act as a negative allosteric modulator of alpha 7 nACh receptors, and radioligand binding and functional data are provided to support this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…4,5 We have previously identified mchlorophenylguanidine (mCPG, 1) as a novel noncompetitive α7 nAChR antagonist chemotype. 6 That is, although 1 lacks affinity for α7 nAChR (i.e., K i > 100 μM at [ 125 I]iodo-MLAlabeled receptors), it blocked the actions of ACh in electrophysiological and in vivo functional assays. 6 In an effort to better understand the action of 1 as a noncompetitive α7 nAChR antagonist, we initiated a structure−activity investigation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 We have previously identified mchlorophenylguanidine (mCPG, 1) as a novel noncompetitive α7 nAChR antagonist chemotype. 6 That is, although 1 lacks affinity for α7 nAChR (i.e., K i > 100 μM at [ 125 I]iodo-MLAlabeled receptors), it blocked the actions of ACh in electrophysiological and in vivo functional assays. 6 In an effort to better understand the action of 1 as a noncompetitive α7 nAChR antagonist, we initiated a structure−activity investigation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 That is, although 1 lacks affinity for α7 nAChR (i.e., K i > 100 μM at [ 125 I]iodo-MLAlabeled receptors), it blocked the actions of ACh in electrophysiological and in vivo functional assays. 6 In an effort to better understand the action of 1 as a noncompetitive α7 nAChR antagonist, we initiated a structure−activity investigation. In a preliminary study, we found that the N 1 -methyl analogue of 1 (i.e., 2) was several times as potent as 1.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of both receptor binding (Kem et al, 1997;Jensen et al, 2003) and functional activity (Gerzanich et al, 1995;Eaton et al, 2003) suggest that nicotine is approximately 100-fold selective for a4b2 versus a7 nAChRs, and the selective a7 antagonist methyllycaconitine (MLA) failed to block thermal antinociception by nicotine in rats (Rao et al, 1996). Nonetheless, MLA did antagonize the antinociceptive effects of intrathecal nicotine in spinal nerveligated rats (Young et al, 2008), and a negative allosteric modulator of a7 nAChRs (meta-chlorophenylguanidine) antagonized nicotine antinociception in a rat tail-flick procedure (Dukat et al, 2010). Moreover, a7 nAChR selective agonists produced antinociception in some rodent models of acute and inflammatory pain (Damaj et al, 1998(Damaj et al, , 2000Wang et al, 2005;Gao et al, 2010), and a7 positive allosteric modulators produced antinociception in mouse models of inflammatory and neuropathic pain (Freitas, et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 99%